MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS MELALUI SENAM OTAK (BRAIN GYM) PADA MAHASISWA - Wahyudi, Ade; Nugroho, Wahyu Setyo (Consilium: Education and Counseling Journal, 2025)
Every educator definitely has a collective goal to improve the quality of education in the archipelago, all students are skilled and can improve their ability to think actively, actively, innovatively and logically so that they are able to receive all information of a scientific nature so that it can be applied in the environment. This research uses classroom action research with a sample size of 10 PJKR 2nd semester students using data collection techniques for student critical thinking tests. Based on this research, it can be concluded that completeness in cycle I was 72.1 to 78.7 in cycle II, while learning completeness increased from 47% to 82%. The research results show that the research objective is to increase critical thinking when the Brain Gym technique is applied.